RETINAL ARTERY OCCLUSION AFTER THERAPEUTIC EMBOLIZATION OF A DURAL ARTERIOVENOUS FISTULA - Silveira e Silva, Diana (2018)
Introduction : Retinal artery occlusive disease is generally caused by atherosclerosis. Dural intracranial fistulae are rare clinical entities with an incidence of 0.29/100.000 adults. Therapeutic embolization is considered according to its anatomical characteristics, and although infrequent, there is risk of secondary retinal branches embolization. Case report: We report the case of a 45-year-old man with history of a hemorrhagic stroke on the left hemisphere in the previous year secondary to an arteriovenous malformation associated with a para-cavernous arteriovenous fistula, who had sudden loss of visual acuity of the left eye 24 hours after therapeutic embolization of a dural para-cavernous arteriovenous fistula. On clinical examination he had a relative afferent pupillary defect on his left eye and fundus examination revealed a cherry red spot with attenuation and segmentation of retinal arterioles of the superior and inferior temporal arcades. The patient started ocular hypotensive drugs and was immediately referred to a hyperbaric oxygen therapy center, where he completed three therapeutic sessions. Despite evidence of retinal reperfusion after one session, final visual acuity was 0.05 in the affected eye. Conclusions: In this case, previous hemorrhagic stroke associated with a para-cavernous fistula was a formal therapeutic indication for embolization. Secondary embolization of retinal artery branches is an infrequent, though possible complication of therapeutic embolization procedures.